Undergraduate Student-Teachers' Perceptions of Remote Learning in the Faculty of Pedagogy at the Lebanese University - Nancy Moussawi; Hanadi Mirza; Fadwa Murdaah (Umm Al-Qura University, 2022)
This study investigates the perceptions of 273 undergraduate student-teachers towards remote learning in the Faculty of Pedagogy at the Lebanese University. Data were collected using a questionnaire and individual interviews. Findings reveal that scores on teaching presence were the highest compared to social, cognitive, metacognitive and affective presence scores. When asked about the teaching presence, participants considered that the teachers' delivery of a variety of topics motivated them to actively participate. As for the social presence, they found that knowing each other prior to Covid 19 pandemic helped them establish a sense of belonging. Participants found that course topics and activities have partially- aroused their curiosity at the cognitive level while metacognitively, they had difficulty asking critical questions and exploring new topics. No positive emotions were reported regarding remote learning. Senior students seem to be affected the most by social, cognitive and metacognitive presences.